A gazdasági siker meghatározói. Cseh Köztársaság 1989-1992: Elméleti fogalmak és hipotézisek (Szociológiai Szemle, 2024)
There are several theories concerning the process of post-communist transition. The theory of ’market transition’ assumes that inequalities will decrease when the redistributive sector of the economy diseappears. The theory of the different forms of capital predicts the conversion of accumulated social capital, i.e., the ’class of redistributors’ are expected to preserve their advantageous positions. The paper tests these hypotheses on the data of two surveys of the same sample, undertaken within the framework of the ’Family 89’ project in 1989 and 1992. It has been found that the best predictions are provided by the theory of the forms of capital, while the change from the state sector to entrepreurship seems to be the most successful strategy.